2021
DOI: 10.1111/ene.14874
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐COVID frequency and short‐term outcome in the Northern Portuguese population

Abstract: Background and purpose: COVID-19-related acute neurological phenotypes are being increasingly recognised, with neurological complications reported in more than 30% of hospitalised patients. However, multicentric studies providing a population-based perspective are lacking. Methods:We conducted a retrospective multicentric study at five hospitals in Northern Portugal, representing 45.1% of all hospitalised patients in this region, between 1 March and 30 June 2020.Results: Among 1261 hospitalised COVID-19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Uncertain evidence for systemic steroids and nasal irrigation (intranasal steroid/mucolytic/decongestant) ( Vaira et al, 2021 ). Seizures Retrospective cohort studies report a seizures prevalence between 0.06% and 1.5% of hospitalized patients ( Rogers et al, 2021 ; Oliveira et al, 2021 ). Many cases with new-onset focal seizures, serial seizures, and status epilepticus have been reported in the literature ( Asadi-Pooya et al, 2021 ).…”
Section: Neurologic Manifestations Of Human Coronavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertain evidence for systemic steroids and nasal irrigation (intranasal steroid/mucolytic/decongestant) ( Vaira et al, 2021 ). Seizures Retrospective cohort studies report a seizures prevalence between 0.06% and 1.5% of hospitalized patients ( Rogers et al, 2021 ; Oliveira et al, 2021 ). Many cases with new-onset focal seizures, serial seizures, and status epilepticus have been reported in the literature ( Asadi-Pooya et al, 2021 ).…”
Section: Neurologic Manifestations Of Human Coronavirus Infectionmentioning
confidence: 99%
“…Seizures rarely represent the presenting symptoms of the infection ( Fasano et al, 2020 ). Retrospective cohort studies have estimated the seizure prevalence ranging from 0.06% to 1.5% of COVID-19 patients ( Oliveira et al, 2021 ; Rogers et al, 2021 ). The etiology of seizures is most likely multifactorial, depending on patients’ characteristics (in particular, comorbidities such as diabetes or kidney disease), severity of the systemic infection that can lead to multiorgan failure, metabolic issues, or severe systemic hypoxemia with anoxic/hypoxic brain injury, drug interactions, specific neurologic involvement with brain damage (encephalitis or cerebrovascular events), and direct viral neuroinvasion ( Emami et al, 2020 ; Asadi-Pooya et al, 2021 ; Pizzi, 2021 ).…”
Section: Neurologic Manifestations Of Human Coronavirus Infectionmentioning
confidence: 99%
“…Although involvement of the respiratory system is the most relevant clinical feature in COVID‐19 patients, neurological symptoms have been widely reported [6−8]. Neurological manifestations associated with SARS‐CoV‐2 infection can affect both the central and peripheral nervous system and range widely from mild taste and smell disturbances to more serious conditions, such as acute cerebrovascular disease, disseminated encephalomyelitis, or Guillain‐Barré syndrome [6−10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that COVID‐19 is associated with a variety of serious neuromuscular complications (Table 2 ), and that these complications worsen the prognosis. 6 However, some of the evidence is based on a small number of case reports or case series, and the possibility that the complications occurred by chance at a time after the onset of COVID‐19 cannot be ruled out. A proof of causality is required to confirm the epidemiological increase in the incidence and/or to elucidate the pathogenic mechanism.…”
Section: Neuromuscular Complicationsmentioning
confidence: 99%